2019
DOI: 10.1101/803676
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A CellAgeClock for expedited discovery of anti-ageing compounds

Abstract: 27 28We aim to improve anti-ageing drug discovery, currently achieved through laborious and 29 lengthy longevity analysis. Recent studies demonstrated that the most accurate molecular 30 method to measure human age is based on CpG methylation profiles, as exemplified by 31 several epigenetics clocks that can accurately predict an individual's age. Here, we 32 developed CellAge, a new epigenetic clock that measures subtle ageing changes in primary 33 human cells in vitro. As such, it provides a unique tool to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…of my US patent application [16], can slow the ticking of the epigenetic clock of human cells in vitro . In the assay used in [120121].…”
Section: Resultsmentioning
confidence: 99%
“…of my US patent application [16], can slow the ticking of the epigenetic clock of human cells in vitro . In the assay used in [120121].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the genome becomes globally hypomethylated, except for certain hypermethylated regions [ 94 , 95 ]. In particular, DNA methylation analysis of 353-specific CpG loci, commonly referred to as the epigenetic clock [ 94 ], allows to estimate DNA methylation (DNAm) or epigenetic age and is currently considered the most reliable biomarker correlating biological and chronological aging [ 96 , 97 ].…”
Section: Ins Retain Age-associated Signatures From the Fibroblast Donormentioning
confidence: 99%
“…Hence, the screen resulted in the identification of one prime candidate, the chalcone Gr-4D, for follow-up studies [79]. Finally, most recently, a methylation-based clock was developed and used to screen for geroprotective compounds in vitro [80].…”
Section: Phenotypic Screening For Geroprotective Compoundsmentioning
confidence: 99%